Sodium selenate biofortification of basil (Ocimum basilicum L.) and peppermint (Mentha × piperita L.) plants grown in a floating system under salinity stress - Cosimo M. Profico; Masoud Hassanpour; Saeid Hazrati; Andrea Ertani; Saeed Mollaei; Silvana Nicola (Journal of Agriculture and Food Research)
Selenium (Se) is an essential micronutrient for mammals, although its availability in plants varies widely due to agricultural methods and environmental conditions. As plants are the primary dietary source of Se, biofortification of aromatic plants is a promising strategy to increase consumer Se intake. Moreover, Se has been shown to play beneficial roles in plants, particularly under abiotic stress conditions. This study aimed to examine the combined effects of Se biofortification (5 μM) and moderate salinity stress (10 mM NaCl) on basil (Ocimum basilicum L.) and peppermint (Mentha × piperita L.) growing in a floating system. The results indicated a higher Se concentration in plants subjected to the Se + NaCl treatment, with approximately 33.01 and 34.87 mg kg−1 in basil and peppermint, respectively. Notably, plants exposed to NaCl and Se accumulated 25 % more Se than those treated with Se alone. The combined treatments significantly increased phenolic content by 45 % in basil (from 6.08 to 9.00 nmol mg−1 fresh weight (FW) and by 62 % in peppermint (from 6.99 to 11.51 nmol mg−1 FW) and increased antioxidant enzyme activity while reducing sodium accumulation. It also increased the activity of antioxidant stress enzymes, alleviating oxidative stress. Se and salinity also altered key essential oil compounds, increasing 1,8-cineole in basil and menthol in peppermint while decreasing both species' eugenol and methyl eugenol levels. In peppermint, both NaCl and Se + NaCl resulted in decreased menthone content and increased menthol content. These findings suggest that Se-enriched basil and peppermint grown under moderate salinity stress can improve Se concentration while maintaining plant quality, addressing nutritional deficiencies in regions with saline conditions.